2016
DOI: 10.1179/2045772315y.0000000010
|View full text |Cite
|
Sign up to set email alerts
|

Tetraparesis as clinical correlate of subacute cervical flexion myelopathy

Abstract: Context:We report the case of a 20-year-old woman who underwent tracheal resection with postoperative chinto-chest suture for 10 days, presenting with severe tetraparesis at our institution. Similar cases have been reported previously, however, not yet in the pathophysiological context of chronic cervical flexion myelopathy (Hirayama syndrome). Findings: Extensive myelopathy at cervical level is the consequence of the fixed cervical spine position due to chin-to-chest suture. Predominantly affected young indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Hirayama disease, also known as flexion myelopathy, is a slowly progressing amyotrophy in the upper extremities. To separate Hirayama disease from the acute myelopathy following neck flexion, it has been proposed that the term subacute flexion myelopathy should be used [ 8 ]. Because patients have usually had their head in a flexed position [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], it has been suggested that neck flexion causes focal compression or stretching of the cervical cord, leading to spinal cord infarction via compromised microvascular perfusion [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hirayama disease, also known as flexion myelopathy, is a slowly progressing amyotrophy in the upper extremities. To separate Hirayama disease from the acute myelopathy following neck flexion, it has been proposed that the term subacute flexion myelopathy should be used [ 8 ]. Because patients have usually had their head in a flexed position [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], it has been suggested that neck flexion causes focal compression or stretching of the cervical cord, leading to spinal cord infarction via compromised microvascular perfusion [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…To separate Hirayama disease from the acute myelopathy following neck flexion, it has been proposed that the term subacute flexion myelopathy should be used [ 8 ]. Because patients have usually had their head in a flexed position [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], it has been suggested that neck flexion causes focal compression or stretching of the cervical cord, leading to spinal cord infarction via compromised microvascular perfusion [ 3 ]. In some subacute flexion myelopathy cases, the lesions shown in MRI scans were rather small [ 2 , 9 ] compared to the extensive lesions of the patients reported here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation